Hubungan Pemberian MP-ASI Dini dengan Status Gizi Bayi Umur 0-6 Bulan di Wilayah Kerja Puskesmas Rowotengah Kabupaten Jember - Risa Wargiana; Latifa Aini Susumaningrum; Iis Rahmawati (UPT Percetakan dan Penerbitan Universitas Jember, 2013)
Nutrition is influenced by some factors, such as giving complementary breastfeeding. Complementary breastfeeding is food or drink contains of nutrition which is given to baby or 6-24 month ages kid for completing the nutrition need besides breastfeeding. The phenomenon in society shows that complementary breastfeeding is given to baby who is under 6 months years old. It is called by the early complementary breastfeeding. The purpose of this observation is to analyze the correlation between giving early complementary breastfeeding and level baby nutrition 0-6 month in work area of Rowotengah community health center in Jember. The design of this observation uses analytic observational. The taking of sample uses non probability sampling technique with simple random sampling. The population of this observation is 0-6 month babies who are listed in Rowotengah community health center in jember which are 496 babies. The determining of the sample uses purposive sampling technique, which are 50 respondents. The processing of the data uses Chi Square test with the credibility is 95% (α=0, 05). The result of the statistic test shows the probability number which is 0,008 (p< 0, 05), so there is correlation between giving early complementary breastfeeding and level baby nutrition 0-6 month in work area of Rowotengah community health center in Jember. Keywords: early complementary breastfeeding, nutrition